The Ulnar Collateral Ligament Responds To Stress In Professional Pitchers. Issue 3 (27th March 2020) - Chalmers, SATPeter Nissen; English, Joy; Cushman, Daniel; Yoon, Steve H.; Schulz, Brian M.; Li, Bernard
Objectives: The ulnar collateral ligament (UCL) is one of the most common sites of injury in baseball pitchers, with 25% of Major League Baseball (MLB) pitchers having undergone surgical reconstruction (UCLR). It remains unknown whether the ligament responds to the stress of pitching. The purpose of this study is to determine the response of the UCL in professional pitchers to pitching and rest through a prospective ultrasonographic study. Methods: This was a prospective study supported by the Major League Baseball Research Committee. All pitchers within a single professional baseball club were enrolled. Pitching exposure history data including number of years pitching and peak pitch velocity were collected. A full ultrasound (US) examination of the ligament was then performed by a single fellowship-trained ultrasonographer with extensive experience with UCL US. This US examination was performed at the beginning of the season, the end of the season, and the beginning of the following season. This US examination included measurement of UCL thickness and valgus laxity, as measured via ulnotrochlear joint opening at 30° of flexion to valgus stress of 10% of the mean pitching torque of 64 Nm. Two US images were saved for each measurement such that all measurements were made twice and analysis was performed on the average. Thirty ultrasounds were measured by a second experienced ultrasonographer to determine inter-rater reliability via intra-class correlation coefficients (ICC). Correlation analyses were performed between pre-season data and pitching exposure data. Paired analyses compared data between pre- and post-season one and between post-season one and pre-season two. Results: 185 total pitchers were included: 94 pitchers were included prior to season one, 83 were included at the end of season one, and 120 pitchers were included prior to season two. Excluding player movement in and out of the active roster, follow-up rate was 70% (46/66) during season one and 91% (49/54) between seasons. These pitchers were 23±4 years old (mean±standard deviation), had 12±6 years pitching experience, and had peak velocity of 95±3 miles per hour. 38 pitchers (21%) underwent UCLR either prior to enrollment or during the study. With examination of US data, ICCs were 0.851 for UCL thickness and 0.906 for UCL laxity at 30°. Peak pitch velocity positively correlated with UCL thickness (p=0.009) and valgus laxity at 30° (p=0.010). Within-subject UCL thickness increased during the season (mean difference [95% confidence intervals] 1.0 [0.3 to 1.7] mm, p=0.006) and decreased during the offseason (0.6 [0.3 to 0.9] mm, p<0.001). Within-subject valgus laxity at 30° increased during the season non-significantly (0.4 [-0.06 to 0.76] mm opening, p=0.069) and decreased significantly during the off season significantly (0.2 [-0.04 to 0.5] mm opening, p=0.039). Conclusion: The ulnar collateral ligament responds to stress and rest in professional pitchers. The UCL thickens and becomes more lax in response to higher pitch velocity and more years of pitching. The UCL thickens and valgus laxity increases with the stress of a single season of pitching, and these effects are partially reversed during the offseason.